Caracteres agronômicos e fisiológicos associados ao progresso do melhoramento genético de trigo no Brasil - Beche, Eduardo (2013)
Knowledge the processes responsible for the progress of genetic gain in grain yield in wheat plant is an essential step for the development of high yield cultivars. The aims of the study were: a) Evaluate the duration of developmental phases in wheat cultivars and quantify the importance of each phase on grain yield and its components. b) characterize physiological and agronomically wheat cultivars released in different decades, to identify selection criteria for continued improvement of genetic progress in Brazil. c) Characterize Brazilian wheat cultivars developed in different decades for the nitrogen use efficiency (NUE). Ten wheat cultivars released from1940 to 2009, were examined for two years in a competition essay (2010 and 2011) and in 2011 an essay in green house was conducted with four nitrogen rates (0, 60, 120 e 180 kg N ha-1). We compared the duration of periods, agronomic and physiological traits (gas exchange) and nitrogen use efficiency (EUN) characters. The Breeding reduced time to anthesis and increased the grain filling, contributing to the increase in thousand kernel weight. The modern cultivars had the period terminal spikelet to anthesis increased (0,68 to 1,35 degree days year-1) over the years, contributing to the increase in the number of grains per spikelet, number of grains per spike, spike dry weight at anthesis and spike fertility index. The increase in grain yield was 29 kg ha-1 yr-1, with a genetic gain of 0,92% yr-1 from 1940 to 2009, this is largely related to the increased of harvest index, number of grains m-2 and biological yield, which were achieved through improving stomatal conductance and photosynthetic rate in pre and post-anthesis and reduced in plant height. The nitrogen uptake efficiency (NUpE) was positively associated with nitrogen use efficiency (NUE) in the absence of fertilization. Nitrogen utilization efficiency (NutE) and NUpE were positively associated with NUE in higher N. The modern cultivars (Quartzo, CD 117, BRS Tangará, BRS 220, BRS 208 and BRS Guamirim) were more efficient in the use of nitrogen and more tolerant to low N input compared to the group formed by BRS 179, BR 23, Toropi and Frontana.